2003
DOI: 10.1007/s00251-003-0573-x
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations of the interleukin-12 receptor beta 1(IL12RB1) and interferon-gamma receptor 1 (IFNGR1) genes are not associated with susceptibility to lepromatous leprosy in Korea

Abstract: Interleukin-12 receptor beta 1 ( IL12RB1), interleukin-12 receptor beta 2 ( IL12RB2), and interferon gamma receptor 1 ( IFNGR1) perform important roles in the host defense against intracellular pathogens such as Mycobacteria. Several mutations within their genes have been confirmed as associated with increased susceptibility to mycobacterial infection. However, the association between mutations of the IL12RB1, IL12RB2, and IFNGR1 encoding genes and lepromatous leprosy has not been studied. This study screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…DNA was extracted using a Puregene DNA Isolation Kit (Gentra Systems, Minneapolis, Minn., USA) following the manufacturer’s protocol. We typed for 5 previously reported SNPs that cause missense mutations in the coding sequence of the IL-12 receptor β1 gene in Koreans [20], namely +705A/G (Q214R, NCBI SNP ID:rs 11575934), +1158T/C (M365T, NCBI SNP ID:rs 375947), +1196G/C (G378R, NCBI SNP ID:rs 401502), +1637G/A (A525T, NCBI SNP ID:rs 11575935) and +1664 C/T (P534S, HGBASE database ID:SNP001745641). For +705A/G genotyping, genomic DNA was amplified using the primer set 5′-ggttaagtgactggtgccaag-3′ and 5′-ctcaaaccactggcctcaag-3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted using a Puregene DNA Isolation Kit (Gentra Systems, Minneapolis, Minn., USA) following the manufacturer’s protocol. We typed for 5 previously reported SNPs that cause missense mutations in the coding sequence of the IL-12 receptor β1 gene in Koreans [20], namely +705A/G (Q214R, NCBI SNP ID:rs 11575934), +1158T/C (M365T, NCBI SNP ID:rs 375947), +1196G/C (G378R, NCBI SNP ID:rs 401502), +1637G/A (A525T, NCBI SNP ID:rs 11575935) and +1664 C/T (P534S, HGBASE database ID:SNP001745641). For +705A/G genotyping, genomic DNA was amplified using the primer set 5′-ggttaagtgactggtgccaag-3′ and 5′-ctcaaaccactggcctcaag-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, polymorphisms in the coding sequence of the IL-12 receptor gene have been reported to be associated with tuberculosis in the Japanese and Moroccan populations [18, 19], but not with leprosy in Koreans [20]. In this study, we examined whether single nucleotide polymorphisms (SNPs) in IL-12 receptor β1 gene are associated with TB in Koreans.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Korean patients, Lee et al [59] found no significant differences in allele frequencies of IL12RB1 between leprosy patients and the control group [59]. Now, in relation to gene in the 5′ flanking region of IL12RB2 , Ohyama et al [60] determined the functional effects of these SNPs on NK-cell activity, including IFN- Îł production and IL-12RB2 gene expression.…”
Section: Cytokines and Leprosymentioning
confidence: 99%
“…In Korean patients, no significant differences were found in allele frequencies IFNGR1 (interferon Îł receptor 1) between leprosy patients and the control group [59]. However, a case report showed that the IFNGR1 polymorphism at position −56T/C was positively associated with an increased susceptibility to leprosy, in Iranian children of the same family [68].…”
Section: Cytokines and Leprosymentioning
confidence: 99%
“…Few investigators showed an association between mutation of IFNGR1 and lepromatous leprosy patient, but others did not support the idea. 10,12 Generally, the diverse genetic results of the disease acquisition might be explained by distinct genetic susceptibly to the disease among different populations. 2 Clearly, the complete absence of IFNGR1 on cell surface induces so profound an immune defect that such mutations are unlikely to explain M. leprae susceptibility in the general population.…”
Section: Introductionmentioning
confidence: 99%